Effect of genomic regions harboring putative lethal haplotypes on reproductive performance in closed experimental selection lines of Nellore cattle - Rodrigues, Gustavo R. D. [UNESP]; Cyrillo, Joslaine N. S. G.; Mota, Lúcio F. M. [UNESP]; Schmidt, Patrícia I. [UNESP]; Valente, Júlia P. S. [UNESP]; Oliveira, Eduarda S. [UNESP]; Albuquerque, Lúcia G. [UNESP]; Brito, Luiz F.; Mercadante, Maria E. Z. [UNESP] (Springer Nature, 2025)
Lethal alleles are mutations in the genome that cause embryonic losses in affected homozygous embryos and, therefore, can negatively influence reproduction rates in commercial populations. Thus, this study aimed to identify genomic regions containing potential lethal haplotypes in Nellore breed; identify candidate genes located within these regions; and investigate the reproductive performance of heterozygous carriers of lethal haplotypes in Nellore cattle. Forty-five genomic regions harboring putative lethal haplotypes were identified, which overlap with 360 genes. Gene ontology analyses of these genes revealed biological processes associated with the development of sexual traits in males and females, key functions of the immune system, energy homeostasis, and embryonic development. The gene networks were involved in metabolic pathways including ovarian steroidogenesis, oocyte meiosis, and insulin secretion. Matings between carrier dam and carrier sire led to a reduction of up to -203.46% in pregnancy success probability, an increase of 275.15% in probability of pregnancy loss, 295.03% for stillbirth occurrence, and 301.40% for pre-weaning mortality when compared to non-carrier dam and sire matings. The results highlight the importance of identifying animals that are carriers of lethal haplotypes to avoid the propagation of these haplotypes in the population.
Keywords: Pregnancy success; Recessive alleles; Stillbirth; Zebu cattle